A comparision of RT-PCR and FISH techniques in molecular diagnosis of Ewing's sarcoma in paraffin-embedded tissue - Berková, A; Dundr, P; Povýsil, C; Melcákova, S; Tvrdík, D (Ceskoslovenska patologie, 2008)
Ewing's sarcoma is relatively uncommon tumor representing 6-8 percent of malignant bone tumors with variable morphology. Cytogenetically, Ewing's sarcomas are characterized by a specific reciprocal chromosomal translocation t(11;22)(q24;q12). The presence of this chromosomal translocation has been detected in approximately 85 percent of the cases. The translocation results in the fusion of EWS gene from chromosome 22 to FLI1 gene at 11q24 which is a member of ETS family of transcription factors. In this study we performed a comparison of two molecular diagnostic strategies, namely RT-PCR and FISH, in fresh, frozen and formalin-fixed paraffin-embedded tissues. We conclude that FISH is a more sensitive technique than RT-PCR for the diagnosis of Ewing's tumors in formalin-fixed paraffin-embedded tissue. In conclusion, molecular pathology techniques, using reverse transcription-polymerase chain reaction (RT-PCR) and/or fluorescence in situ hybridization (FISH) are valuable diagnostic tools for evaluation of undifferentiated small round-cell tumors like Ewing's sarcoma.
Keywords: protein EWS vázající RNA; Proto-Oncogene Protein c-fli-1; Soft Tissue Neoplasms; Ewingův sarkom; Humans; translokace genetická; In Situ Hybridization, Fluorescence; zalévání tkání do parafínu; genetické markery; RNA-Binding Protein EWS; fúzní onkogenní proteiny; Chromosomes, Human, Pair 22; polymerázová řetězová reakce s reverzní transkripcí; Retroviridae Proteins, Oncogenic; Translocation, Genetic; lidé; Reverse Transcriptase Polymerase Chain Reaction; nádory měkkých tkání; Oncogene Proteins, Fusion; Retroviridae - proteiny onkogenní; Sarcoma, Ewing; protoonkogenní protein c-fli-1; lidské chromozomy, pár 22; hybridizace in situ fluorescenční; Paraffin Embedding; Genetic Markers